Propositional Dynamic Logic for Planning - Benevides, Mario Folhadela; de Oliveira, Anna Moreira (Anais do Workshop Brasileiro de Lógica (WBL); 2020: Anais do I Workshop Brasileiro de LógicaDO - 10.5753/wbl.2020.11454, 2020)
This paper presents an on going work on Propositional Dynamic Logic PDL in which atomic programs are STRIPS actions. We think that this new framework is appropriate to reasoning about actions and plans when dealing with planning problem. Unlike, PDL atomic programs, STRIPS actions have pre-conditions and post-conditions. We propose a novel operator of action composition that takes in account the features of STRIPS actions. We propose an axiomatization and prove its soundness. Completeness, decidability and computational complexity are left as future work.